Mapping groundwater potential in a section of Cocinetas Basin, Alta Guajira, Colombia (2017)
The Alta Guajira region in northernmost Colombia is the driest area in the country, getting less than 200 mm of average rainfall year-round. Many communities of mainly indigenous people inhabit this area, and heavily rely on groundwater from handcrafted wells and rainwater as a source for their cattle, irrigation and consumption. Few studies have been performed in this area to understand the chemistry, spatial distribution, and recharge processes of ground water. Therefore, the sustainability and quality of aquifers currently used is unknown. In this work, we carried out a remote sensing and GIS-based analysis of the Alta Guajira region, integrating DEM-derived slope, drainage density and lineament density analyses with existing geologic maps, vegetation and surface temperatures obtained from multispectral satellite images. A groundwater potential map was calculated by combining these thematic layers, with their information normalized to a single quantitative scale from 0 to 1, giving each parameter equal weight on the analysis. Four areas of groundwater potential were defined: very low, low, medium and high potential. The resulting areas were then compared with the locations of existing shallow and deep groundwater wells, and natural water springs; this comparison showed a correlation between groundwater potential and spatial location of wells. This study resulted in the estimation of prospect areas where further field work and analytical techniques (like geochemical analyses and recharge estimation) should be carried out to further understand the hydrogeology. Said areas are mostly located on the southern slope of the Macuira and Jarara ranges, and on the flat south-west part of the study area.